2008
DOI: 10.1183/09031936.00149607
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term response to corticosteroid therapy in chronic beryllium disease

Abstract: Chronic beryllium disease (CBD) is a granulomatous disorder that affects the lung after exposure to beryllium. The present study reports short-and long-term evolution of granulomatous and fibrotic components in eight patients with severe CBD receiving corticosteroid therapy.Eight patients with confirmed CBD were studied at baseline, after initial corticosteroid treatment (4-12 months), at relapse and at the final visit. Beryllium exposure, Glu 69 (HLA-DPB1 genes coding for glutamate at position b69) polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 19 publications
(14 reference statements)
2
29
0
5
Order By: Relevance
“…In six of the eight patients, the treatment appeared to stop progressive fibrosis. The study by MARCHAND-ADAM et al [19] confirms the earlier report by SEELER [20] and strongly suggests that cases of beryllium disease that could be detected through medical screening programmes would benefit from corticosteroid therapy.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…In six of the eight patients, the treatment appeared to stop progressive fibrosis. The study by MARCHAND-ADAM et al [19] confirms the earlier report by SEELER [20] and strongly suggests that cases of beryllium disease that could be detected through medical screening programmes would benefit from corticosteroid therapy.…”
supporting
confidence: 81%
“…As a result, corticosteroids and other immunosuppressive medication are considered to be the standard of treatment, and there never have been nor will there ever be controlled trials. The study by MARCHAND-ADAM et al [19], which is the best report of treatment in patients with a confirmed immunological diagnosis of CBD, confirms the earlier report of SEELER [20] and describes computed tomography (CT) findings that appear responsive to corticosteroids. Eight patients with immunologically confirmed CBD were treated with corticosteroids; a 26% improvement was noted in vital capacity and a 15% improvement was seen in diffusion capacity of the lung for carbon monoxide.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Current treatment of CBD relies on both beryllium exposure cessation and corticosteroid therapy. Corticosteroid therapy is efficient on the granulomatous component and leads to a significant clinical, radiological, biological and functional improvement [6]. However, the efficacy of corticosteroids doesn't last: relapses occur following cessation of therapy or dose lowering and long-duration treatment with possible severe side-effects is often necessary.…”
mentioning
confidence: 99%
“…However, the efficacy of corticosteroids doesn't last: relapses occur following cessation of therapy or dose lowering and long-duration treatment with possible severe side-effects is often necessary. Eventually, some patients might not respond as expected to corticosteroids, or develop progressive lung fibrosis despite this treatment [6,7].…”
mentioning
confidence: 99%